2014
DOI: 10.1002/cphc.201400083
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Electrochemical Cells Containing Bulk Metal

Abstract: The development of improved energy-storage devices, as well as corrosion prevention and metal-electrofinishing technologies, requires knowledge of local composition and transport behaviour in electrolytes near bulk metals, in situ and in real time. It remains a challenge to acquire such data and new analytical methods are required. Recent work shows that magnetic resonance imaging (MRI) is able to map concentration gradients and visualise electrochemical processes in electrochemical cells containing bulk metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…(5), (8) and (9), agree with the observed values within an order of magnitude for 2d MRI(xy), 2d MRI(yz), 2d MRI(zy), 3d MRI(xyz), 3d CSI(yz) and 2d CSI(y). In fact, discrepancies between observed and derived S ac /S ab ratios range only by factors of 0.7 to 2.8 across various MRI and CSI images (see Table.1).…”
Section: Intensity Ratio Formulae For Bulk Metal Mri and Csisupporting
confidence: 82%
See 1 more Smart Citation
“…(5), (8) and (9), agree with the observed values within an order of magnitude for 2d MRI(xy), 2d MRI(yz), 2d MRI(zy), 3d MRI(xyz), 3d CSI(yz) and 2d CSI(y). In fact, discrepancies between observed and derived S ac /S ab ratios range only by factors of 0.7 to 2.8 across various MRI and CSI images (see Table.1).…”
Section: Intensity Ratio Formulae For Bulk Metal Mri and Csisupporting
confidence: 82%
“…Using optimal alignment of the bulk metal (electrodes), relative to B 1 , recent studies have successfully demonstrated and highlighted bulk metal MRI albeit, primarily applied to batteries and electrochemical cells. [5][6][7][8][9] Though unanticipated at the time, the recent bulk metal MRI findings eased the implementation of MRI of liquid electrolyte, by helping mitigate adverse effects due to the metal in the vicinity of lithium, zinc and titanium electrodes, yielding fresh insights. 7,8,[31][32][33] Similar benefits may be expected to accrue for MRI based radiology of soft tissues with embedded metallic implants (pacemeakers, prosthetics, dental implants, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since all MRI and CSI images to follow were acquired with the given phantom's bc faces normal (⊥, perpendicular) to B 1 , these images bear the imprint of having no contribution from these faces to the magnetic resonance (MR) signal, [5][6][7][8] since B 1 penetration into the metal is maximal when it is parallel ( ) to the metal surface, and minimal when ⊥ metal surface. 1,5,6 For details on the MRI experiments, including the nomenclature, the reader is referred to Methods section 6.2.…”
Section: Introductionmentioning
confidence: 99%
“…In situ spectroscopic monitoring of electrochemical reactions [3] has employed av ariety of techniques,including UV/Vis,infrared (IR), and Raman spectroscopies.T he spectroscopic detection of metal ions is most commonly achieved through the use of molecular sensors, [4] which are typically probed using fluorescence spectroscopy or microscopy,enabling detection of the presence,concentration and environment of metal ions through am odulation of the life time,anisotropy or intensity of the fluorescence signal of the molecular probe.O ptical methods cannot be used on optically opaque samples and concerns arise that molecular sensors may affect the chemistry of the system under study. Nuclear magnetic resonance (NMR) avoids both of these difficulties as it is able to detect the presence and concentration of metal ions in solution, either directly for NMRactive nuclei such as 7 Li or 23 Na or, indirectly,t hrough the measurement of 1 HNMR relaxation times of solvent molecules, [5] which can be sensitive to the presence and speciation of metal ions.I nm agnetic resonance imaging (MRI), this information becomes spatially resolved through the use of magnetic field gradients.[5b] However,there are very few MRI studies mapping the distribution of metal ions near bulk metals.[6] This is largely due to difficulties with performing MRI experiments on samples containing bulk metals,a s ar esult of the presence of magnetic susceptibility artefacts and generation of eddy currents in the bulk metal.[7] While, recent studies have shown that it is possible to overcome these problems by careful control of electrode orientation and cell geometry, [7,8] another limitation, is that there are very few nuclei that can be readily imaged by MRI. In fact, the vast majority of nuclei are difficult, or impossible,t od irectly image with MRI, due to low sensitivity and abundance,aswell as short T 2 relaxation times.Hence,indirect detection, by 1 H MRI, offers aunique opportunity for insight into many more systems of interest than are currently accessible.A lso,a s 1 H …”
mentioning
confidence: 99%
“…[7] While, recent studies have shown that it is possible to overcome these problems by careful control of electrode orientation and cell geometry, [7,8] another limitation, is that there are very few nuclei that can be readily imaged by MRI. In fact, the vast majority of nuclei are difficult, or impossible,t od irectly image with MRI, due to low sensitivity and abundance,aswell as short T 2 relaxation times.Hence,indirect detection, by 1 H MRI, offers aunique opportunity for insight into many more systems of interest than are currently accessible.A lso,a s 1 H …”
mentioning
confidence: 99%